2017
DOI: 10.1039/c7ra01940h
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional application of a new malonyltransferase NbMaT1 towards diverse aromatic glycosides from Nicotiana benthamiana

Abstract: Recently, owing to the important pharmaceutical properties of malonylated glycosides, their chemoenzymatic synthesis using malonyltransferase has received significant attention. In the present study, a new malonyltransferase, NbMaT1, was identified from Nicotiana benthamiana. Extensive enzymatic assays revealed its significant substrate tolerance based on HPLC-UV and HR-MS analyses.Moreover, 16 of the tested glycosides including flavone glycosides, flavonol glycosides, dihydroflavone glycosides, isoflavone gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Based on our current results, we infer that NaMaT1 is a malonyl-CoA:DTG malonyltransferase, which may catalyze three consecutive malonylation steps, as reported for Dm3MaT2, which catalyzes consecutive dimalonyl transfers to anthocyanin ( Suzuki et al, 2004 ). Notably, two characterized MaTs in the Nicotiana genus, NbMaT1 and NtMaT1, accept aromatic glycosides as substrate ( Taguchi et al, 2005 ; Liu et al, 2017 ). Phylogenic and protein identity analysis showed that NbMaT1 and NtMaT1 share the highest sequence similarity with NaMaT2 and NaMaT3, about 90%, whereas the identity with NaMaT1 is 80% ( Figure 2A and Figure 2—figure supplement 1B ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our current results, we infer that NaMaT1 is a malonyl-CoA:DTG malonyltransferase, which may catalyze three consecutive malonylation steps, as reported for Dm3MaT2, which catalyzes consecutive dimalonyl transfers to anthocyanin ( Suzuki et al, 2004 ). Notably, two characterized MaTs in the Nicotiana genus, NbMaT1 and NtMaT1, accept aromatic glycosides as substrate ( Taguchi et al, 2005 ; Liu et al, 2017 ). Phylogenic and protein identity analysis showed that NbMaT1 and NtMaT1 share the highest sequence similarity with NaMaT2 and NaMaT3, about 90%, whereas the identity with NaMaT1 is 80% ( Figure 2A and Figure 2—figure supplement 1B ).…”
Section: Discussionmentioning
confidence: 99%
“…The isomers might have resulted from different glycosylation positions of the flavones, or malonylation could have occurred at various positions of the glucose or apiosyl. The 7-O position of the flavones and 6"-position glucose has been reported as the most frequent site of glycosylation and acylation, respectively [62,63]. For example, formononetin glucoside malonate isomers were found to show two acylation points on the sugar group identified as 7-O-β-D-glucoside 6"-O-malonate and 7-O-β-D-glucoside 4"-O-malonate [64].…”
Section: Flavones Decorations/modificationsmentioning
confidence: 99%